Living on the Edge: Physiological and Kinetic Trade-Offs Shape Thermal Tolerance in Intertidal Crabs From Tropical to Sub-Antarctic South America - Faria, Samuel Coelho; Bianchini, Adalto; Lauer, Mariana Machado; Zimbardi, Ana Lúcia Ribeiro Latorre; Tapella, Federico; Romero, Maria Carolina; McNamara, John Campbell (Frontiers in Physiology, 2020)
Temperature is an important abiotic factor that drives the evolution of ectotherms owing to its pervasive effects at all levels of organization. Although species’ thermal tolerance is environmentally driven within a spatial cline, it may be constrained over time due to differential phylogenetic inheritance. At the limits of thermal tolerance, hemolymph oxygen is reduced and lactate formation is increased due to mismatch between oxygen supply and demand; imbalance between enzyme flexibility/stability also impairs the ability to generate energy. Here, we characterized the effects of lower (LL50) and upper (UL50) critical thermal limits on selected descriptors of aerobic and anaerobic metabolism in 12 intertidal crab species distributed from northern Brazil (»7.8° S) to southern Patagonia (»53.2° S), considering their phylogeny. We tested for (i) functional trade-offs regarding aerobic and anaerobic metabolism and LDH kinetics in shaping thermal tolerance; (ii) influence of shared ancestry and thermal province on metabolic evolution; and (iii) presence of evolutionary convergences and adaptive peaks in the crab phylogeny. The tropical and subtropical species showed similar systemic and kinetic responses, both differing from the sub-Antarctic crabs. The lower UL50’s of the sub-Antarctic crabs may reflect mismatch between the evolution of aerobic and anaerobic metabolism since these crabs exhibit lower oxygen consumption but higher lactate formation than tropical and subtropical species also at their respective UL50’s. LDH activity increased with temperature increase, while KmPyr remained fairly constant; catalytic coefficient correlated negatively with thermal niche. Thermal tolerance may rely on a putative evolutionary trade-off between aerobic and anaerobic metabolism regarding energy supply, while temperature compensation of kinetic performance is driven by thermal habitat as revealed by the LDH affinity/efficiency equilibrium. The overall physiological evolution revealed two homoplastic adaptive peaks in the sub-Antarctic crabs with a further shift in the tropical/subtropical clade. The physiological traits at UL50 have evolved in a phylogenetic manner while all others were more plastic. Thus, shared inheritance and thermal environment have driven the crabs’ thermal tolerance and metabolic evolution, revealing physiological transformations that have arisen in both colder and warmer climes, especially at higher levels of biological organization and phylogenetic diversity.